2019
DOI: 10.12659/msm.916687
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia is a Risk Factor for the Incidence and Severity of Drug-Induced Liver Injury (DILI): A Retrospective Population-Based Study in China

Abstract: Background A Chinese population-based study aimed to investigate the risk factors for the incidence and severity of drug-induced liver injury (DILI) from Chinese herbal medicines and conventional Western medicines. Material/Methods Liver biopsy and routine laboratory testing, including serum lipid measurements, was performed on 465 patients, including 168 patients with DILI and 297 patients without DILI. Histological grading of DILI used the METAVIR scoring system and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Innate/adaptive immune responses have key roles in the biological mechanisms of DILI 41 and could also could affect blood cell levels. Consistent with the results of other studies, we found associations between dyslipidemia, drinking, and the severity of DILI 2 . The detailed mechanisms have been described in our previous study 2 , 41 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Innate/adaptive immune responses have key roles in the biological mechanisms of DILI 41 and could also could affect blood cell levels. Consistent with the results of other studies, we found associations between dyslipidemia, drinking, and the severity of DILI 2 . The detailed mechanisms have been described in our previous study 2 , 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results of other studies, we found associations between dyslipidemia, drinking, and the severity of DILI 2 . The detailed mechanisms have been described in our previous study 2,41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is an important organ for drug metabolism and transformation as well as for overall metabolism and immunity. The incidence of DILI and HILI has seen a steady increase over recent years, and DILI and HILI has become a common and serious drug-induced condition worldwide [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high prevalence of GIT symptoms can be explained by obesity itself, which is a risk factor for hepatic steatosis [36,37], abdominal pain, nausea, vomiting, and diarrhoea [37]. In addition, hepatic steatosis may be associated with changes in drug metabolism, which contribute to the manifestation of GIT-related symptoms [38]. Although CNS-related symptoms have not yet been physiologically elucidated, obesity has been associated with sleep disorders [39], which could explain the sleepiness presented by the patients in our study.…”
Section: Discussionmentioning
confidence: 99%